Crop water stress index and forage quality relationships in alfalfa - Abd Halim, Mohd Ridzwan; Buxton, D. R.; Hattendorf, M. J.; Carlson, R. E. (American Society of Agronomy, 1990)
Recent developments in assessment of plant-water stress employ infrared thermometers to measure the difference between air and canopy foliage temperature (Tc − Ta). Crop Water Stress Index (CWSI), which normalizes Tc − Ta values for climatic variability, is related to forage yields of alfalfa (Medicago sativa L.). The objective of this study was to determine whether forage quality of alfalfa also is related to CWSI. ‘Apollo II’ alfalfa was grown in 100-L potometers set into the ground and protected by a movable rainout shelter. Plants were watered either weekly or twice weekly to 112, 100, 88,76, and 64% of field capacity during 2 yr. Daily readings of canopy and air temperature were taken, and vapor-pressure deficits were determined from the time plants were 15 cm tall until harvest. Plants were harvested after 5 wk of regrowth and were divided into stem bases (lower six nodes and internodes), stem tops, and leaves before forage quality analyses were conducted. Dry-matter yield and plant maturity declined linearly with increasing CWSI (8 = 0.86 and 0.65, respectively). Leaf-to-stem ratio increased with increasing CWSI (8 = 0.51), but year effects, in addition to waterstress effects, were evident. In vitro digestible dry matter (IVDDM) in stem bases increased with CWSI (r2 = 0.78), but leaf IVDDM was not significantly related to CWSI. Crude protein (CP) concentration in stem bases increased with CWSI (r2 = 0.86), whereas leaf CP concentration declined quadratically with increasing CWSI (r2 = 0.51). Total-herbage CP concentration was not significantly related to CWSI. Neutral-detergent fiber concentration in stem bases, leaves, and total herbage declined with increasing CWSI (r2 = 0.89, 0.75, and 0.69, respectively). Thus, models based solely on plant quality-CWSI relationships may not be adequate for predictive purposes because, often, year effects were not removed or coefficients of determination were low.